THE ANALYSIS OF TOOTH AREA CHARACTERISTIC INFLUENCE ON WORKING CHARACTERISTICS OF ASYNCHRONOUS MOTOR - Valery Marmyshev; Irina Romanenko; Maksim Danilov (Вестник Северо-Кавказского федерального университета)
The proportions of asynchronous motor tooth area were calculated based on verifying computation. The motor working characteristics with varied combination of modified tooth area characteristic were calculated. The slot width and height of stator and rotor, the air-gap value were modified. The analysis of working characteristics, obtained after tooth area configuration changing, was produced. It was determined, that rotor lot proportions influence on working characteristics is the largest.